GPR17: Molecular modeling and dynamics studies of the 3-D structure and purinergic ligand binding features in comparison with P2Y receptors - Ranghino Graziella; Abbracchio Maria P; Parravicini Chiara; Fantucci Piercarlo (BMC Bioinformatics, 2008)
Abstract Background GPR17 is a G-protein-coupled receptor located at intermediate phylogenetic position between two distinct receptor families: the P2Y and CysLT receptors for extracellular nucleotides and cysteinyl-LTs, respectively. We previously showed that GPR17 can indeed respond to both classes of endogenous ligands and to synthetic compounds active at the above receptor families, thus representing the first fully characterized non-peptide "hybrid" GPCR. In a rat brain focal ischemia model, the selective in vivo knock down of GPR17 by anti-sense technology or P2Y/CysLT antagonists reduced progression of ischemic damage, thus highlighting GPR17 as a novel therapeutic target for stroke. Elucidation of the structure of GPR17 and of ligand binding mechanisms are the necessary steps to obtain selective and potent drugs for this new potential target. On this basis, a 3-D molecular model of GPR17 embedded in a solvated phospholipid bilayer and refined by molecular dynamics simulations has been the first aim of this study. To explore the binding mode of the "purinergic" component of the receptor, the endogenous agonist UDP and two P2Y receptor antagonists demonstrated to be active on GPR17 (MRS2179 and cangrelor) were then modeled on the receptor. Results Molecular dynamics simulations suggest that GPR17 nucleotide binding pocket is similar to that described for the other P2Y receptors, although only one of the three basic residues that have been typically involved in ligand recognition is conserved (Arg255). The binding pocket is enclosed between the helical bundle and covered at the top by EL2. Driving interactions are H-bonds and salt bridges between the 6.55 and 6.52 residues and the phosphate moieties of the ligands. An "accessory" binding site in a region formed by the EL2, EL3 and the Nt was also found. Conclusion Nucleotide binding to GPR17 occurs on the same receptor regions identified for already known P2Y receptors. Agonist/antagonist binding mode are similar, but not identical. An accessory external binding site could guide small ligands to the deeper principal binding site in a multi-step mechanism of activation. The nucleotide binding pocket appears to be unable to allocate the leukotrienic type ligands in the same effective way.